ANXIETY LEVELS OF COPD SUFFERERS ARE STABLE IN INDONESIA - Akbar, Yudi; Mursal, Mursal; Amni, Rahmalia (Universitas Islam Negeri Alauddin Makassar, 2022)
Physiological changes due to inflammation in patients with (COPD) significantly led to a decrease in carbon dioxide levels in the blood. It can trigger physiological changes in the form of anxiety to depression. This study aimed to identify the level of anxiety in patients with stable COPD. The study was using quantitative descriptive design, sample of 70 patient, questionnaire STAI (State-Trait Anxiety Inventory). The majority of respondents are male (85.2%), aged> 65 years (35.5%) had quit smoking (97.5%) with duration of smoking cessation> 2 years (49.0%), and the majority COPD patients had> 2 years (60.0%). Most of the patients had a moderate level of anxiety (42.8%), and mild (30.0%), or severe (27.2%). Anxiety is not treated immediately will risk causing disturbances in various aspects of life of patients. Thus, it is important for patients detection and treatment of anxiety quickly and precisely along with the medical treatment of COPD.